To review the effect of tightened and loosened torque on two different implant-Abutment connection designs: A scanning electron microscope study - Jyoti Arneja; Salil Pawah; Amit Gupta; Manisha; Chetan Pathak; Neha Jain (Wolters Kluwer Medknow Publications, 2021)
Introduction: It is crucial to take care of stability between various implant parts for the general success rate of the reconstruction. Component fit, saliva contamination, machining accuracy, and screw preload influence the steadiness of implant-abutment connection. Loosening of abutment screws has been a well-known technical problem. Aim: The aim of this study was to gauge repeated tightening and loosening torque on two commercially available implant/abutment connection designs. Study Design: This was an in vitro study. Methodology: A total of 32 implant analogs samples using a metal die with, metal ring of 20mm x 20mm x 20mm in size and a hole in the center were prepared. For both the groups, the implant analog was axially threaded within bases. They were clasped at an edge parallel to the standard minimal bone position. A 35 N/cm torque was enforced, each implant and abutment connection in both the groups using toque ratchet. After 20 min, screws were loosened and detorque measurement was recorded up to ten times. Scanning electron microscope micrographs of selected screws also are presented. SPSS (21.0 version) was used for analyzing data. Results: The mean residual torque for Group 1 was − 51.45 and Group 2 was − 43.29. The RTq (%) was found to be significantly less (0.028*) among Group 2: conical connection as compared to Group 1: butt joint connection. Conclusion: The loosening torque was significantly less in conical connection as compared to butt joint connection.